Partisan Patriotism in the American Presidency: American Exceptionalism, Issue Ownership, and the Age of Trump. Issue 3 (4th May 2019) - Gilmore, Jason; Rowling, Charles M.
Abstract : This study employs issue ownership theory to examine the partisan dynamics surrounding the idea of American exceptionalism in presidential discourse. We conducted a content analysis of invocations of American exceptionalism in all major U.S. presidential addresses—domestic and foreign—from the end of World War II through Trump's 1st year in office. We find that even though Republicans have traditionally claimed ownership of American exceptionalism, patterns in presidential discourse tell a very different story. Specifically, our results show (a) in domestic contexts, Republican and Democratic presidents were very similar in their invocations of American exceptionalism during the Cold War but that Democrats have held a substantial advantage over Republicans throughout the post–Cold War era, including on issue areas that Republicans are perceived to "own" (e.g. national security); (b) in foreign contexts, Democrats have been much more outspoken in their embrace of American exceptionalism throughout both the Cold War and post–Cold War; and (c) President Trump has diverged significantly, both in substance and frequency, from his Democratic and Republican predecessors in his invocation of American exceptionalism. We reflect on the implications of these findings on our broader understanding of issue—and trait—ownership, presidential discourse, and American exceptionalism in American politics.